Основные показатели термомеханической защиты высоковольтных конденсаторов в зарядно-разрядных цепях мощных емкостных накопителей энергии от аварийных сверхтоков - Баранов, Михаил Иванович (НТУ "ХПИ", 2014)
Приведены результаты расчетной оценки ограничений установленными в зарядно-разрядных цепях мощных емкостных накопителей энергии (ЕНЭ) защитными высоковольтными керамическими резисторами амплитуд аварийного сверхтока, давления и температуры в локальной зоне внутреннего электрического пробоя маслонаполненного высоковольтного импульсного конденсатора указанных цепей ЕНЭ и развития в его жидком диэлектрике сильноточного плазменного канала искрового разряда.

The results of calculation estimation of limitations are resulted set in the charge-bit chains of powerful capacity stores of energy (CSE) the protective high-voltage ceramic resistors of amplitudes of emergency very large currents, pressures and temperatures in the local area of internal electric hasp of the oil-immersed high-voltage impulsive condenserof the indicated chains of CSE and development in his liquid dielectric of heavy-current plasma channel of a spark discharge.
The main indicators of thermomechanical protect of high voltage capacitors in the charge-discharge circuits powerful capacitive energy storage from emergency overcurrent
Keywords: защитный резистор; оценка ограничений тока; давление; температура; high-voltage condenser; protective resistor